Immunotherapies to Nano-Immunotherapies: Advances in Immune Targeting in Bladder Cancer - Beatriz Ramos; Dakota Rogers (Annals of Urologic Oncology)
Bladder cancer is among most common malignancies worldwide, with significant morbidity and mortality. Conventional treatment strategies for bladder cancer include transurethral resection, radical cystectomy and chemotherapy. However, the complex immune landscape of bladder cancer involves innate and adaptive immune components that either promote or suppress tumor progression. Upregulation of checkpoint molecules like PD-L1 and recruitment of immunosuppressive cells, contribute to immune evasion and treatment resistance. Immune checkpoint inhibitors such as nivolumab, pembrolizumab, avelumab, and atezolizumab have shown promising results in clinical trials and have been approved for metastatic and high-risk bladder cancer. Additionally, Bacillus Calmette-Guérin (BCG) immunotherapy has long been in use as bladder cancer treatment. Furthermore, natural killer cell-based therapies and novel immune targets like TIGIT and CD155 are under investigation to enhance anti-tumor immunity. However, challenges such as toxic side-effects, variable response rates and the need for predictive biomarkers persists. Nanotechnology offers promising solutions to improve immunotherapy outcomes. Recent advances include the use of gold nanoparticles, TLR agonist-loaded nanoparticles, and exosome-based delivery systems to boost immune responses. Additionally, nanovaccine strategies incorporating tumor-associated antigens and immune adjuvants show potential for personalized cancer immunotherapy. Here, we discuss the immune landscape of bladder cancer, explore the emerging immunotherapies being used as bladder cancer treatment, and discuss the advantages of using nanoparticles as carriers of immunotherapies against bladder cancer. By optimizing combination strategies, identifying novel immunotherapeutic targets, and leveraging nanotechnology for precision medicine, future holds great promise in improving the efficacy of immunotherapies and alleviating bladder cancer burden.